If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = (2x + 1)(x + -3) Reorder the terms: 0 = (1 + 2x)(x + -3) Reorder the terms: 0 = (1 + 2x)(-3 + x) Multiply (1 + 2x) * (-3 + x) 0 = (1(-3 + x) + 2x * (-3 + x)) 0 = ((-3 * 1 + x * 1) + 2x * (-3 + x)) 0 = ((-3 + 1x) + 2x * (-3 + x)) 0 = (-3 + 1x + (-3 * 2x + x * 2x)) 0 = (-3 + 1x + (-6x + 2x2)) Combine like terms: 1x + -6x = -5x 0 = (-3 + -5x + 2x2) Solving 0 = -3 + -5x + 2x2 Solving for variable 'x'. Combine like terms: 0 + 3 = 3 3 + 5x + -2x2 = -3 + -5x + 2x2 + 3 + 5x + -2x2 Reorder the terms: 3 + 5x + -2x2 = -3 + 3 + -5x + 5x + 2x2 + -2x2 Combine like terms: -3 + 3 = 0 3 + 5x + -2x2 = 0 + -5x + 5x + 2x2 + -2x2 3 + 5x + -2x2 = -5x + 5x + 2x2 + -2x2 Combine like terms: -5x + 5x = 0 3 + 5x + -2x2 = 0 + 2x2 + -2x2 3 + 5x + -2x2 = 2x2 + -2x2 Combine like terms: 2x2 + -2x2 = 0 3 + 5x + -2x2 = 0 Factor a trinomial. (3 + -1x)(1 + 2x) = 0Subproblem 1
Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3Subproblem 2
Set the factor '(1 + 2x)' equal to zero and attempt to solve: Simplifying 1 + 2x = 0 Solving 1 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 2x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 2x = 0 + -1 2x = 0 + -1 Combine like terms: 0 + -1 = -1 2x = -1 Divide each side by '2'. x = -0.5 Simplifying x = -0.5Solution
x = {3, -0.5}
| 7a-a-5a= | | .75(8x-4)+.5(6x+4)= | | 3X-2X-4= | | 2n^2-143n-390=0 | | .75(8x)= | | -4(66x+166)=11x-4x | | 3(2x+3)=39 | | 3x+7y=36 | | .75(8x-4)= | | (9x-5)(81x^2-90x+25)=0 | | 2*-6-3=y | | 9m-2n-2m+4n= | | 7x-8+3x=8x+2 | | -3(5a+4)= | | 3x^4-2x^2-8=0 | | 5*-2+2=y | | 3m-2n-5m+6n= | | 6a-3a-5a= | | y=5*2+2 | | y=5*0+2 | | y=5*-2+2 | | 9(x-1)+4(x+1)=20-4x | | -10*1+1=y | | p(x)=95-3x | | 11n+18=9n-3 | | -10*0+1=y | | 4x^2+26x-8=0 | | -10*0+1= | | -10*-1+1=y | | a^3-4a^2+5a-20= | | a^3-4a^2+5a-20=0 | | -10*-5+1=y |